Type 2 diabetes mellitus‐related genetic polymorphisms in microRNAs and microRNA target sites (MicroRNAs中与2型糖尿病相关的基因多态性及microRNA靶位). (15th April 2014) - Gong, Weijing; Xiao, Di; Ming, Guangfeng; Yin, Jiye; Zhou, Honghao; Liu, Zhaoqian
Abstract MicroRNAs (miRNAs) are important endogenous regulators in eukaryotic gene expression and a broad range of biological processes. MiRNA‐related genetic variations have been proved to be associated with human diseases, such as type 2 diabetes mellitus (T2DM). Polymorphisms in miRNA genes (primary miRNAs, precursor miRNAs, mature miRNAs, and miRNA regulatory regions) may be involved in the development of T2DM by changing the expression and structure of miRNAs and target gene expression. Genetic polymorphisms of the 3′‐untranslated region (UTR) in miRNA target genes may destroy putative miRNA binding sites or create new miRNA binding sites, which affects the binding of UTRs with miRNAs, finally resulting in susceptibility to and development of T2DM. Therefore, focusing on studies into genetic polymorphisms in miRNAs or miRNA binding sites will help our understanding of the pathophysiology of T2DM development and lead to better health management. Herein, we review the association of genetic polymorphisms in miRNA and miRNA targets genes with T2DM development.